PERANAN SIKAP MENTAL TERHADAP KOMITMEN KARYAWAN MATERIALS DEPARTEMENT PADA HOTEL GRAND HYATT BALI DI NUSA DUA: PERANAN SIKAP MENTAL TERHADAP KOMITMEN KARYAWAN MATERIALS DEPARTEMENT PADA HOTEL GRAND HYATT BALI DI NUSA DUA - Ida Bagus Gede Udiyana; Ida Bagus Ngurah Wimpascima (STIMI Handayani Denpasar, 2006)
This research analys role of mental attitude consisting the indicator (1) attitude to the company rules, (2) Obedience to the company rules, (3) The activity of doing the job, (4) The accuracy in using the office equipment, (5) The work relationship of the employees to the commitment of material department employees at Grand hyatt Hotel Nusa Dua Bali. The purpose of this researce are : (1) To know mental attitude building which is given by Grand Hyatt Hotel Nusa Dua Bali, (2) To know employees commitment of materials department pg Grand Hyatt Hotel Nusa Dua Bali.